Bridging Community and Hospital Waste Management: Insights from Birendranagar, Surkhet - Budha, Neelam; Koirala, Madhav Prasad (Journal of UTEC Engineering Management, 2025)
Hospital waste management is critical in developing countries like Nepal to mitigate health and environmental risks, promote infection control, and ensure the safety of healthcare workers and the community. This study assessed waste management practices in two hospitals in Birendranagar, Surkhet, focusing on issues with labeling, cleanliness, and waste segregation. The methodology adopted was a literature survey, questionnaire, observation, and interview. It is indicated that concrete vaults, sharp pits, and labeled storage chambers may be built for better handling of waste. Some of the proper segregation practices resulted in less hazardous waste and more non-hazardous and recyclable waste. Even though both hospitals had policies related to waste management, there were no appropriate facilities, which resulted in the mixing of waste and the absence of labeled chambers. The study recommended color-coded chambers, which must be followed along with treatment methods including autoclaves and needle cutters. Karnali Province Hospital at 55% occupancy produced an average of 398.09 kg/day waste that reaches 723.8 kg/day at full capacity, while at 50% occupancy, Karnali Care International Hospital produced 78.80 kg/day waste, reaching a projection of 157.6 kg/day at 100%. To improve hospital waste management in Nepal, better segregation can reduce health risks and generate income from recyclables. Properly securing biogas plants and utilizing food waste for biogas production could lower waste management costs. This study emphasizes the need for efficient waste strategies, infrastructure enhancements, and sustainable practices for economic and environmental benefits.